Humoral response to SARS-CoV-2 infection among liver transplant recipients. Issue 4 (5th January 2022) - Becchetti, Chiara; Broekhoven, Annelotte G C; Dahlqvist, Géraldine; Fraga, Montserrat; Zambelli, Marco Fabrizio; Ciccarelli, Olga; Saouli, Anne-Catherine; Trizzino, Arianna; Banz, Vanessa; Dufour, Jean-François; Roukens, Anna H E; Torres Morales, Shessy P; et al.
Abstract : Objective: Immunosuppressive agents are known to interfere with T and/or B lymphocytes, which are required to mount an adequate serologic response. Therefore, we aim to investigate the antibody response to SARS-CoV-2 in liver transplant (LT) recipients after COVID-19. Design: Prospective multicentre case–control study, analysing antibodies against the nucleocapsid protein, spike (S) protein of SARS-CoV-2 and their neutralising activity in LT recipients with confirmed SARS-CoV-2 infection (COVID-19-LT) compared with immunocompetent patients (COVID-19-immunocompetent) and LT recipients without COVID-19 symptoms (non-COVID-19-LT). Results: Overall, 35 LT recipients were included in the COVID-19-LT cohort. 35 and 70 subjects fulfilling the matching criteria were assigned to the COVID-19-immunocompetent and non-COVID-19-LT cohorts, respectively. We showed that LT recipients, despite immunosuppression and less symptoms, mounted a detectable antinucleocapsid antibody titre in 80% of the cases, although significantly lower compared with the COVID-19-immunocompetent cohort (3.73 vs 7.36 index level, p<0.001). When analysing anti-S antibody response, no difference in positivity rate was found between the COVID-19-LT and COVID-19-immunocompetent cohorts (97.1% vs 100%, p=0.314). Functional antibody testing showed neutralising activity in 82.9% of LT recipients (vs 100% in COVID-19-immunocompetent cohort, p=0.024). Conclusions: Our findings suggest that the humoral response of LT recipients is only slightly lower than expected, compared with COVID-19 immunocompetent controls. Testing for anti-S antibodies alone can lead to an overestimation of the neutralising ability in LT recipients. Altogether, routine antibody testing against separate SARS-CoV-2 antigens and functional testing show that the far majority of LT patients are capable of mounting an adequate antibody response with neutralising ability.